A collection and transcription of Chishawasha songs of the Roman Catholic Church Mass - Chipendo, Bliss Tafadzwa (Midlands State University, 2018)
The major purpose for this study was to collect and transcribe Chishawasha songs of the Roman Catholic Church in Zimbabwe for preservation and later use in the church. The research employed a case study in the qualitative form. St Theresa Roman Catholic Church Cathedral in Gweru was chosen as the case study because that is where the researcher attends Mass. Face to face interviews and participant observation was used to collect data. Collected data was presented in the form of music scores transcribed in staff notation. Major findings of the study indicate that Chishawasha songs are getting extinct because they are not documented or preserved through notation or any other means. Also choristers and composers in the Roman Catholic Church lack enthusiasm and skills to transcribe and notate the church music. The songs composed and sung in church are taught through rote. Songs in the Chishawasha hymn book are written in poetic form such that they can only be sung by those who already know them. The lack of the culture of notating songs in the Catholic Church results in the extinction of most church songs. Furthermore, the younger generation is not much interested in songs that are in call and response and also in two part harmony like the Chishawasha songs, but in songs which include modern forms of harmony (soprano, alto, tenor and bass). This study collected and transcribed 17 Chishawasha songs performed during Mass. There is therefore need to develop a culture of notating music in the Roman Catholic Church in Zimbabwe. It can therefore be recommended that The Catholic Music Composers Association should organize and conduct workshops to help composers and choristers be able to read and write music as this will help in automatically documenting the music for future generations.